2019
DOI: 10.1186/s12903-019-0738-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Investigation of molecular biomarker candidates for diagnosis and prognosis of chronic periodontitis by bioinformatics analysis of pooled microarray gene expression datasets in Gene Expression Omnibus (GEO)

Abstract: Background Chronic periodontitis (CP) is a multifactorial inflammatory disease. For the diagnosis of CP, it is necessary to investigate molecular biomarkers and the biological pathway of CP. Although analysis of mRNA expression profiling with microarray is useful to elucidate pathological mechanisms of multifactorial diseases, it is expensive. Therefore, we utilized pooled microarray gene expression data on the basis of data sharing to reduce hybridization costs and compensate for insufficient mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…identi ed CD19 and CD79A as the molecular biomarker candidates and pathogenesis of chronic periodontitis [26]. The above evidence suggested that B lymphocytes play an important role in the development of periodontitis.…”
Section: Discussionmentioning
confidence: 95%
“…identi ed CD19 and CD79A as the molecular biomarker candidates and pathogenesis of chronic periodontitis [26]. The above evidence suggested that B lymphocytes play an important role in the development of periodontitis.…”
Section: Discussionmentioning
confidence: 95%
“…Of the 81 potential biomarkers presented in an experimental gingivitis study [ 5 ], only 14 and 2 genes overlap with cohorts 1 and 2, respectively. Data sets from 5 previous periodontitis studies [ 5 6 21 22 23 ] were also compared, and poor consistency was also observed. No genes commonly detected in all 5 studies, only 9 genes were common to 4 of the data sets, and 46 genes were common to 3 of the data sets.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study investigated molecular biomarker candidates and biological pathways of chronic periodontitis using pooled datasets in the Gene Expression Omnibus (GEO) database, and identified 123 common differently expressed genes (DEGs), including 81 upregulated genes and 42 downregulated genes 32 . Several of the identified genes were also among the top hits in our SMR analysis.…”
Section: Discussionmentioning
confidence: 99%